Secondary Piggyback Intraocular Lens for Correcting Refractive Surprise Post Silicone Oil Removal: Poster Presentation - Case Report - Resident - Budiman; Juanarta, Pieter; Knoch, Andrew M.H.; Sugiarti, Emmy Dwi; Tjokrovontjo, Ludwig Melino (Majalah Oftalmologi Indonesia, 2023)
Introduction : Pseudophakic refractive error can be caused by IOL malposition and inaccurate biometric examination. Treatment consists of IOL exchange, refractive laser correction, and secondary piggyback IOL. Secondary Piggyback IOL consist of customized IOL implantation on ciliary sulcus. Case Illustration : A Male, 62 years old, complains of blurry right eye. He underwent retinal surgery with silicone oil tamponade surgery 5 years ago and underwent silicone oil evacuation, phacoemulsification, and intraocular lens implantation one year later. The visual acuity of the right eye was 1/60 with BCVA of 0.2. He was diagnosed with Pseudophakia of both eyes and Hypermetropia Surprise of the right eye. He was planned to undergo piggyback intraocular lens implantation in the right eye (Figure 1). The visual acuity one week after operation of the patient's right eye was 0.32 (Figure 2). Discussion : Biometric examination in eye with silicon oil tamponade have longer axial length, causing pseudophakic refractive errors. Treatments consist of IOL replacement, refractive laser correction, and piggyback IOL implantation. IOL replacement has a high risk and requires quite high operator skills. Refractive laser correction is performed in small refractive errors. Piggyback IOL implantationis easier, safer, have more accurate IOL power, and reversible. Conclusion : Power of the intraocular lens is influenced by axial length, keratometry reading, lens thickness, and other parameters. Axial length measurement in patients with silicone oil tamponade requires greater accuracy to prevent pseudophakic refractive errors. IOL Piggyback implantation procedure is an alternative in person that can’t undergo laser correction or IOL exchange.